جدل الشفاهية والوعي الكتابي في نماذج من الشعر الجاهلي: دراسة هيرمينوطيقية - عشا، علي مصطفى محمد (جامعة عين شمس - كلية الآداب, 2019)
This research studies the images writing in selected samples of pre- Islamic poetry, and displays some features of orally theory that emerged from the western critical mind it trying to approach the ”Homery issue”, and access to the memory laws and construction systems, poetic creativity orally, and orally initial receiving, in compared with models of the efforts of some Arab researchers in their approach to the doubt issue of Pre-Islamic Poetry. This research tries to reveals the ontology of language, and the importance of modern science language to visibility the poetic creativity and make intellectually and aesthetically approach ; as the language is the existence house, or the being house, as Martin Heidegger states. The research reveals writing images that contacted - through the image - with “Stand on Talal.” The Pre-Islamic poets consistently resoles the ”Talal” to the writing. This research tries to make approach of their writing awareness through the transformation of Nature /” Talal” to Writing/ Culture in the poetic image. This research take analytical and hermeneutics method to study the writing images and it representations range of the writing awareness at the Pre-Islamic poets.
يدرس هذا البحث صور الكتابة في نماذج مختارة من الشعر الجاهلي، ويعرض بعض ملامح النظرية الشفاهية التي انبثقت عن العقل النقدي الغربي في محاولته مقاربة المسألة الهومرية، والوصول إلى قوانين الذاكرة، ونظم الإنشاء والإبداع الشعري الشفاهي، والتلقي الأولي الشفاهي لهذا الشعر، بالمقارنة مع نماذج لجهود بعض الباحثين العرب في مقاربتهم لقضية الشك في الشعر الجاهلي. ويحاول البحث الكشف عن أنطولوجيا اللغة، وأهمية علم اللغة الحديث في جلاء الإبداع الشعري ومقاربته فكريا وجماليا؛ باعتبار اللغة مسكن الوجود، أو بيت الكينونة على حد تعبير مارتن هيدجر. ويرصد البحث صور الكتابة التي اتصلت- عبر الصورة الشعرية - بالوقفة الطللية؛ إذ دأب الشعراء الجاهليون على تشبيه الأطلال الدارسة بالكتابة، ومقاربة الوعي الكتابي لديهم خلال تحول الطبيعة/ الأطلال إلى كتابة / ثقافة في الصورة الشعرية. ويتخذ البحث منهجا تحليليا تأويليا في دراسته لصور الكتابة، ومدى تمثيلها للوعي الكتابي لدى الشعراء الجاهليين.
Keywords: الشعر العربي -- العصر الجاهلي -- النقد الأدبي -- الأسلوب الأدبي